Distribution and management of Fusarium wilt (Fusarium oxysporum f.sp. lentis) of lentil (Lens culinaris Medikus) in Central Highlands of Ethiopia - Bedasa, T. (Haramaya University, 2018)
Fusarium wilt of lentil (F. oxysporum f.sp. lentis) causes huge lentil yield losses in central highlands of Ethiopia. In this study, extensive wilt survey of eight major lentil-growing districts, viz. Adaa, Aleltu, Lume, Gimbichu, Minjar-Shenkora, Siyadebrena Wayu, Moretina-jiru and Ensaro in central highlands of Ethiopia was conducted during the 2017cropping season. The study of the objectives were to: 1) assess the distribution of lentil Fusarium wilt in the central highlands of Ethiopia; 2) determine the extent of seed infection due to lentil Fusarium wilt pathogen on seed lots collected from different sources in the central highlands of Ethiopia; and 3) evaluate the effect of lentil varieties and seedbed types as components of integrated management option. Data of the survey revealed 100% mean wilt prevalence and 32.8% mean wilt incidence were observed. The highest (75%) and the lowest (2%) wilt incidence were recorded in Moretina-jiru and Lume, respectively. Morphological and cultural assessment of 192 isolates of wilt causal agents showed hihgest frequencies of Fusarium oxysporum f.sp. lentis (100%) followed by Rhizoctonia spp. (23.4%) and Sclerotium rolfsii (3.0%). A factorial experiment involving lentil variety and seedbed type, each at four levels, was carried out in a split-plot design with three replications. The four lentil varieties were ILL-590 (susceptible check), Alemaya, Derash and Denbi, and four seedbed types were flat bed, open raised bed, tieraised bed and farmer’s practice. Among the seedbed types, raised seedbed exhibited relatively lower disease incidence than others. Interaction of the varieties and seedbed types was significant in wilt reduction. The highest wilt incidence (ca. 82.0%) was recorded on ILL-590, susceptible lentil line, planted on flat bed; whereas, the lowest (ca. 8.8%) Fusarium wilt incidence was noted on cv. Derash planted on raised bed. A combination of cv. Derash and raised bed gave significantly (P < 0.05) higher grain yield (3827.0 kg/ha) than all other treatment combinations at Chefe Donsa. Unlike Chefe Donsa, raised bed contributed significantly (P < 0.05) higher grain yield of not only cv. Derash but also cv. Alemaya than all other treatment combinations at Debre Zeit. Significantly (P < 0.05) lower grain yields (in the order of 68.0 kg ha-1) were obtained from integration of the susceptible genotype (ILL-590) with flat bed than all other treatment integration irrespective of the trial locations. The highest (1018.0% unit/days) in AUDPC values were obtained by flat seedbed type and ILL-590, while the lowest (342.4% unit/days) in AUDPC values were obtained by raised seedbed type and Derash variety at Debre Zeit. Wilt incidence and AUDPC values were significant and negatively correlated with yield parameters. Lentil seed infection due to Fusarium oxysporum f.sp. lentis ranged from 0 to 22.2%. It was concluded that using resistant variety with raised seedbed significantly reduced Fusarium wilt incidence and gave reasonably high yields. The future research work should focus on screening several lentil genotypes for source of resistance.